2006
DOI: 10.1021/es052149m
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Atmospheric Deposition of PCBs to the Delaware River Watershed

Abstract: Atmospheric deposition can be an important source of PCBs to aquatic ecosystems. To develop the total maximum daily load (TMDL) for polychlorinated biphenyls (PCBs) for the tidal Delaware River (water-quality Zones 2-5), estimates of the loading of PCBs to the river from atmospheric deposition were generated from seven air-monitoring sites along the river. This paper presents the atmospheric PCB data from these sites, estimates direct atmospheric deposition fluxes, and assesses the importance of atmospheric de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 17 publications
2
38
1
Order By: Relevance
“…OCP concentrations measured in this study were found to be generally lower than those measured in long-term monitoring programs of the Integrated Atmospheric Deposition Network, the New Jersey Atmospheric Deposition Network, and the Lake Ontario Atmospheric Deposition Study (see Table 2) (Pagano, 2005;Sun et al, 2007;Totten et al, 2006). Acadia National Park's distance from large-scale current or historical use of agricultural pesticides in comparison to other site locations may explain the relatively low contaminant levels reported in this study.…”
Section: Pop Concentrationscontrasting
confidence: 48%
“…OCP concentrations measured in this study were found to be generally lower than those measured in long-term monitoring programs of the Integrated Atmospheric Deposition Network, the New Jersey Atmospheric Deposition Network, and the Lake Ontario Atmospheric Deposition Study (see Table 2) (Pagano, 2005;Sun et al, 2007;Totten et al, 2006). Acadia National Park's distance from large-scale current or historical use of agricultural pesticides in comparison to other site locations may explain the relatively low contaminant levels reported in this study.…”
Section: Pop Concentrationscontrasting
confidence: 48%
“…28,29 These data sets were all therefore collected under a Quality Assurance Project Plan (QAPP) approved by the US EPA and using EPA method 1668A. 7 Atmospheric PCBs were measured by active 30 (Figure 1). 8 PCB 11 levels in these products are many orders of magnitude lower than the levels of ΣPCBs found in carbonless copy paper in 1972, when PCB concentrations were reported as high as 64.7 mg g −1 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…PCBs are an industrial product; there are no known natural sources. Atmospheric depositions, runoff from the land, and food chain transport (Morrison et al, 2002;Totten et al, 2006;Davis et al, 2007) have been regarded as the major sources of PCBs in aquatic environments. Urban runoff from local watersheds is a particularly significant pathway for PCB entry into the lagoon.…”
Section: Fig 2 Ternary Diagram Of the Distribution Of Low Mid And mentioning
confidence: 99%